2014
DOI: 10.1111/liv.12646
|View full text |Cite
|
Sign up to set email alerts
|

Bridging all oral DAA therapy from wait time to post‐liver transplant to improve HCV eradication?

Abstract: Waiting for direct antiviral agents combinations, our findings not only support the use of sofosbuvir plus ribavirin as the first-line treatment in all patients on the LT waiting list, but also suggest to bridge treatment to the post-transplant period in case HCV RNA undetectability for at least 30 days has not been achieved at the time of LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
(22 reference statements)
4
22
0
Order By: Relevance
“…Thus, if planning treatment of patients up to the time of LT, the goal should be to have sufficient time to achieve at least 30 days of HCV RNA negativity prior to LT. There are reports of continuing therapy post-LT in patients who received a very short course of pre-LT therapy, but the clinical scenarios where this is necessary are unclear [11].…”
Section: Key Pointsmentioning
confidence: 99%
“…Thus, if planning treatment of patients up to the time of LT, the goal should be to have sufficient time to achieve at least 30 days of HCV RNA negativity prior to LT. There are reports of continuing therapy post-LT in patients who received a very short course of pre-LT therapy, but the clinical scenarios where this is necessary are unclear [11].…”
Section: Key Pointsmentioning
confidence: 99%
“…Some transplant groups promote the so-called bridging treatment, which consists on starting antiviral treatment on the waiting list (even if the expected time to a LT is short), and continue therapy immediately after LT [70,71]. To date, this issue still remains as a controversial unanswered question that will have to be addressed in well-defined clinical trials in order to justify the benefit of this strategy.…”
Section: Antiviral Treatment On the Waiting List For Liver Transplantmentioning
confidence: 97%
“…Despite recent advances in antiviral treatment, no data have been published on the use of the latest DAAs for preventive treatment. Donato et al 30 described a case where treatment with SOF and RBV was started 1 week prior to LT, and maintained during and after surgery. The authors found no adverse effects and no need to suspend treatment, even though the patient ultimately required retransplant.…”
Section: Preventive Treatmentmentioning
confidence: 99%